Student’s previous conceptions about energy trough science, technology and society - Salvador, Heloiza (2020)
Studies about the Science, Technology and Society (STS) triad have been gaining ground in the school scientific environment. In this sense, this approach provides an interdisciplinary teaching learning, providing students with a critical and social view of scientific and technological themes. Thus, energy is related to several relevant aspects of society and thus receives prominence in science education and its technologies. Thus, this research aims to study and understand the previous conceptions presented by high school students about the STS triad and how they relate it to issues present in their daily lives, more specifically about the energy theme. For this, a qualitative research was developed with the application of an open questionnaire to a class of the first year of high school. From the content analysis of Bardin (2008), students' answers were classified into categories with theoretical basis in the works of Bazzo et al (2003) and Bucussi (2007). In the end, it was concluded that the STS approach is not very present in the school and that the students cannot relate it to everyday subjects maintaining a consistent line of reasoning.